Multilayered glycoproteomic analysis reveals the hepatotoxic mechanism in perfluorooctane sulfonate (PFOS) exposure mice. (1st January 2021) - Li, Dapeng; Jiang, Lilong; Hong, Yanjun; Cai, Zongwei
Abstract: Perfluorooctane sulfonate (PFOS) is one of the most widely used and distributed perfluorinated compounds proven to cause adverse health outcomes. Datasets of ecotoxico-genomics and proteomics have given greater insights for PFOS toxicological effect. However, the molecular mechanisms of hepatotoxicity of PFOS on post-translational modifications (PTMs) regulation, which is most relevant for regulating the activity of proteins, are not well elucidated. Protein glycosylation is one of the most ubiquitous PTMs associated with diverse cellular functions, which are critical towards the understanding of the multiple biological processes and toxic mechanisms exposed to PFOS. Here, we exploit the multilayered glycoproteomics to quantify the global protein expression levels, glycosylation sites, and glycoproteins in PFOS exposure and wild-type mouse livers. The identified 2439 proteins, 1292 glycosites, and 799 glycoproteins were displayed complex heterogeneity in PFOS exposure mouse livers. Quantification results reveal that 241 dysregulated proteins (fold change ≥ 2, p < 0.05) in PFOS exposure mouse livers were involved in the lipid and xenobiotic metabolism. While, 16 overexpressed glycoproteins were exclusively related to neutrophil degranulation, cellular responses to stress, protein processing in endoplasmic reticulum (ER). Moreover, the interactome and functional network analysis identified HP and HSP90AA1 as the potential glycoprotein biomarkers. These results provide unique insights into a deep understanding of the mechanisms of PFOS induced hepatotoxicity and liver disease. Our platform of multilayered glycoproteomics can be adapted to diverse ecotoxicological research. Graphical abstract: Image 1 Highlights: Multilayered glycoproteomic techniques were adapted to uncover PFOS induced hepatoxic mechanism. Dysregulated glycoproteome exclusively involved in ER stress and neutrophil degranulation. HSP90AA1 and HP were potential glycobiomarkers for PFOS hepatotoxicity. This platform can be adapted to diverse ecotoxicological research.